Efektivitas Penggunaan Video Animasi Powtoon pada Materi Jamur terhadap Hasil Belajar Siswa Kelas X - Widi Dwitia; Eko Sri Wahyuni; Laili Fitri Yeni (Bioscientist : Jurnal Ilmiah Biologi, 2024)
The aim of this research is to determine the effectiveness of using powtoon animation videos on mushroom material on the learning outcomes of class X students at SMA Negeri 1 Pemangkat. The form of research used is Quasy Experimental Design with a Non-Equivalent Control Group Design research design. The samples for this research were classes X C (control class) and X D (experimental class). Intact Group sampling technique. The instrument used is a multiple choice test with a total of 20 questions. The average value of learning outcomes for experimental class students was 15.22, while the average value of learning outcomes for control class was 14.28. Based on the results of parametric statistical tests (t-test), the results obtained are tcount 3.13 > ttable 2.03 so it can be concluded that H0 is rejected and Ha is accepted, where there are differences in the learning outcomes of students who are taught using Powtoon animation video media and students who are taught using charta media. . Based on the results of the effect size of learning using powtoon animation video media, it obtained a value of 0.78 in the medium category, meaning that the effectiveness of learning using powtoon animation video media on mushroom material was classified as moderate in improving the learning outcomes of class X students at SMA Negeri 1 Pemangkat by 28.23%.